Ultrasound diagnostics of consequences of traumatic injuries of liver - E. E. Tyuryumina; E. A. Chizhova; V. A. Shanturov; R. R. Gumerov (Acta Biomedica Scientifica, 2013)
The results of ultrasound diagnostics of consequences of traumatic injuries of liver in 122 patients were analyzed. Contours, structure and. texture of intrahepatic formations depended on the type of tissue substrate (haematoma, haemobylema, bylema), terms of formation and infection of traumatic focus. At aseptic course of haematomas and haemobylemas of liver we divided pathological process into 4 stages: stage of latest hemorrhage, stage of formed clot, hemolytic stage and reparative stage. The differences at the infection way of development started from the second week after appearance of intrahepatic injury on the stage of "bacterial lysis of a clot" and. incapsulation. Ultrasound semiotics of intrahepatic bylemas depended only on the infection of contents.